Coffee pest resistant to common insecticide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A new strain of the coffee berry borer is threatening coffee production world-vvide because it is resistant to the most commonly used coffee insecticide. In 1989, scientists on the South Pacific Ocean island of New Caledonia found that the pest had...